ANALYSIS OF FACTORS AFFECTING FAIR REPLACEMENT VALUE OF LAND ACQUISITION FOR ROAD WIDENING IN RONGGUR NIHUTA, PANGURURAN DISTRICT, SAMOSIR REGENCY - Tamba, Natalis Pardamean; Sukaria Sinulingga; Sugiharto Pujangkoro (Journal of Innovation Research and Knowledge, 2023)
The purpose of this research is to analyze factors affecting fair replacement value of land acquisition for road widening in Ronggur Nihuta, Pangururan District, Samosir Regency. This type of research is associative research with a quantitative approach. Population in this study is fair replacement value for each area on road widening in Ronggur Nihuta section which is determined and issued by the Office of Public Appraisal Services assigned by the Regional Secretariat of the Samosir Regency Government. The samples to be used in this study are 46 taken using a random sampling technique. The data analysis method uses a partial (t) test. The results of the study show that physical loss has a significant effect on fair replacement value of land acquisition for road widening in Ronggur Nihuta, Pangururan District, Samosir Regency. Non physical loss has a significant effect on fair replacement value of land acquisition for road widening in Ronggur Nihuta, Pangururan District, Samosir Regency.